PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI ZAT ADITIF - Senja, Andhini Muthia; Fauziah, An Nuril Maulida (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2023)
This research aimed to determine the problem based learning implementation model toward students' critical thinking skills on the material of additives. This research used pre-experimental design with one group pretest posttest. The subjects’ in this research were 31 students’ of VIII B class in Public Junior High School 27 Gresik. Data collection technique of pretest and posttest, observation, and provision of questionnaires. The data was analyzed quantitatively. The results of the N-Gain calculation showed that the application of problem based learning model increased students' critical thinking skills on the additives material with a high category. Descriptive analysis on learning activities by the given treatment had a high percentage result. The conclusion obtained was science learning using a problem based learning model on the additives material can improve students’ critical thinking skills.